Understanding the Causes of Reading Comprehension Deficits in Bruneian Primary Schools: Insights from Teacher Perspectives (International Journal of Linguistics and Indigenous Culture, 2026)
Reading is very important for students’ school study, especially their language learning. Some students, especially those in primary schools, have various reading problems all over the world and Brunei is not an exception. However, this problem has not caused enough attention in Brunei’s academic research. This paper is such an effort to explore the causes contributing to reading comprehension deficits in primary school students in Brunei from teachers’ perspectives. The research is based on survey responses from English language teachers in primary schools, who highlight several concerns: limited time for reading-focused lessons, a significant gap between reading and comprehension skills, insufficient reading resources, and a lack of parental support. The findings show that although reading programmes are implemented in schools, they may not be sufficient to bridge the reading and comprehension gap without proper support. This paper concludes with recommendations to improve reading comprehension in schools.